Future Fab. - Mouli, C. (IEEE spectrum)
This paper presents the software suite dubbed automated manufacturing technology (AMT) that monitors and controls the hundreds of steps wafers must pass through on their way to becoming Pentium, Itanium, and Core 2 Duo processors, as well as other high-end Intel microprocessors. The AMT suite has four major components: the manufacturing execution system, the process control automation framework, the engineering analysis framework, and the material handling and tool control. Each is composed of several programs, and each of those programs controls a different part of the chip-making process. The paper also presents how the grid improves the manufacturing flow and the R&D process by looking at a 25-piece lot of experimental wafers called Lot X500